{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# 6 - Winchell Daniel Homework 6 Due Oct 3 2006 3:00 am Inst...

This preview shows pages 1–3. Sign up to view the full content.

Winchell, Daniel – Homework 6 – Due: Oct 3 2006, 3:00 am – Inst: Karakhanyan 1 This print-out should have 24 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. The due time is Central time. version 312 001 (part 1 of 1) 10 points Find the value of f 0 (4) when f ( x ) = 5 3 x 3 / 2 + 2 x 1 / 2 . 002 (part 1 of 1) 10 points Determine f 0 ( x ) when f ( x ) = - 3 x 8 + 7 x 4 + 2 π. 1. f 0 ( x ) = - 24 x 7 + 28 x 3 2. f 0 ( x ) = - 3 x 8 + 28 x 3 + 2 3. f 0 ( x ) = - 24 x 7 + 28 x 3 + 2 πx 4. f 0 ( x ) = - 24 x 7 + 7 x 4 5. f 0 ( x ) = - 24 x 7 + 28 x 3 + 2 π 003 (part 1 of 1) 10 points Find the x -coordinate of all points on the graph of f ( x ) = x 3 - 4 x 2 - 16 x + 4 at which the tangent line is horizontal. 1. x -coord = - 4 2. x -coord = 4 3. x -coord = 4 3 4. x -coord = - 4 3 5. x -coords = 4 3 , - 4 6. x -coords = - 4 3 , 4 004 (part 1 of 1) 10 points Find the derivative of f ( x ) = 2 x 1 4 - x - 1 4 - 6 . 1. f 0 ( x ) = 2 x 1 2 - 1 4 x 3 4 2. f 0 ( x ) = 2 x 1 4 + 1 4 x 3 4 3. f 0 ( x ) = 2 x 1 2 + 1 4 x 5 4 4. f 0 ( x ) = 2 x 1 2 + 1 3 x 5 4 5. f 0 ( x ) = 2 x 1 2 - 1 4 x 5 4 005 (part 1 of 1) 10 points Find the value of f 0 ( - 1) for f ( x ) = 3 x 2 - 1 x 2 + 6 . 006 (part 1 of 1) 10 points Determine the derivative of f when f ( x ) = 3 x + 1 3 x . 1. f 0 ( x ) = 3 x + 1 3 x 2. f 0 ( x ) = 1 2 3 x + 1 x 3 x 3. f 0 ( x ) = 3 x + 1 x 3 x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Winchell, Daniel – Homework 6 – Due: Oct 3 2006, 3:00 am – Inst: Karakhanyan 2 4. f 0 ( x ) = 1 2 3 x - 1 x 3 x 5. f 0 ( x ) = 3 x - 1 x 3 x 6. f 0 ( x ) = 1 2 3 x - 1 3 x 007 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = ( x 2 + 3)(1 - 3 x 3 ) . 1. f 0 ( x ) = 2 x 2 + 27 x 3 - 15 x 4 2. f 0 ( x ) = 2 x - 27 x 2 - 15 x 4 3. f 0 ( x ) = 2 x 2 - 27 x 3 - 15 x 4 4. f 0 ( x ) = 2 x - 27 x 2 - 15 x 3 5. f 0 ( x ) = 2 x + 27 x 2 - 15 x 3 008 (part 1 of 1) 10 points Find the derivative of g when g ( x ) = x + 2 x + 1 (2 x - 9) .
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern